To determine a analytical protocol for chlorpyrifos in soil - Quoc Tat, Truong; Minh Vien, Duong (VNU Journal of Science: Natural Sciences and Technology, 2017)
The objective of this study was to determine a analytical protocol which get high performance for chlorpyrifos in agricultural soil at laboratory conditions. The experiment was carried out through the steps:  testing the performance of two methods extract soxhlet and mix; testing the performance of the two sample condensation methods by nitrogene gas blowing and allowed to evaporate naturally; testing the performance of the two columns type (Alumina and Florisil); testing the performance of the five types of solvents (Acetone, Toluen:Acetone with ratio 2:1, add water and mix soil sample before add Toluen:Acetone with ratio 2:1, DCM and Diethyl ether); final content analysis of chlorpyrifos by GC/MS-QP2010. Experimental result determined a analytical protocol for chlorpyrifos get 40-50% performance. This protocol includes extraction sample with shaking method, Diethyl ether has been selected for use to extract chlorpyrifos from soil, filtration of Alumina column (small column) was selected to clean extract solution and sample condensation method by allowed to evaporate naturally.